Penerapan Metode MAUT Dalam Sistem Pendukung Keputusan Untuk Pemilihan Supplier - Yulinawati, Yulinawati; Resmi, Mohzen Gito; Kaniawulan, Ismi (LPPM STIKI MALANG, 2024)
This study aims to develop a decision support system (DSS) to assist companies in selecting the most suitable supplier based on relevant criteria. The method used in this research is the Multi-Attribute Utility Theory (MAUT), chosen for its ability to accelerate the decision-making process with a reasonable level of accuracy. The system is designed to evaluate various important criteria in supplier selection. To ensure the system design and development process is structured and systematic, the Waterfall method was applied as a reference in the design and development of the DSS using the MAUT method. The results of this study show that the DSS-based MAUT method can provide valid recommendations, with CV. Bintang Gemilang selected as the best supplier with a utility score of 0.8.